2021
DOI: 10.1007/s00253-021-11258-2
|View full text |Cite
|
Sign up to set email alerts
|

Microwave-assisted hydrotropic pretreatment as a new and highly efficient way to cellulosic ethanol production from maize distillery stillage

Abstract: Aim of the study was to assess the suitability of the combined use of microwave radiation and sodium cumene sulfonate under optimized process conditions for the preparation of maize stillage biomass as a raw material for the production of cellulosic ethanol. The key parameter guaranteeing a high level of lignin removal from biomass (ca. 44%) was concentration of hydrotrope. Even at high biomass concentration (16% w/v) and a cellulase enzyme dose of about 4 filter-paper units/g, maize stillage biomass subjected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…However, the absence of inhibitor formation in hydrotropic pretreatments was reported by several researchers. It was found that there was no inhibitor produced in microwave-assisted hydrotropic pretreatment of maize distillery stillage and in hydrotropic pretreatment of cotton stalk . Moreover, although some literatures reported the absence of inhibitor production in their microwave-assisted pretreatment, in this kinetic model, the formation of inhibitors was represented by the term of formation of soluble lignin from lignin (eq b) as well as formation of soluble hemicellulose from hemicellulose (eq ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the absence of inhibitor formation in hydrotropic pretreatments was reported by several researchers. It was found that there was no inhibitor produced in microwave-assisted hydrotropic pretreatment of maize distillery stillage and in hydrotropic pretreatment of cotton stalk . Moreover, although some literatures reported the absence of inhibitor production in their microwave-assisted pretreatment, in this kinetic model, the formation of inhibitors was represented by the term of formation of soluble lignin from lignin (eq b) as well as formation of soluble hemicellulose from hemicellulose (eq ).…”
Section: Resultsmentioning
confidence: 99%
“…16,19,20 The combination of microwave heating and hydrotrope in biomass pretreatment was also reported. 21 It was reported that the cellulose concentration increased, while 44% of lignin was removed from the distillery stillage which was pretreated with sodium cumene sulfonate under microwave heating. 21 Moreover, although the main objective of the pretreatment is lignin removal, it is important to note that pretreatment with chemical agents as well as microwave heating also resulted in the solubilization of cellulose and hemicellulose.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Waste distillery stillage biomass is a by-product of the technology of production of first generation ethanol involving starch raw materials. Some technologies are marked by barothermal processing of the raw material (5–6 atm, 50 min) affecting the structure of lignocelulose 35 . The effectiveness of the delignification of sugarcane bagasse using sodium xylene sulfonate (NaXS) also increases by ca.…”
Section: Discussionmentioning
confidence: 99%
“…The authors used microwave radiation to overcome the limitation of aqueous salt solution. 135 High concentrations of ethanol (≥40 g L −1 ) were obtained from biomass using this process, achieving 95% of the theoretical fermentation yield. This microwave-assisted hydrotropic fractionation method removed 44% of lignin from biomass without generating any fermentation inhibitors.…”
Section: Phenol-4-sulfonic Acid (Psa) He Et Al Demonstratedmentioning
confidence: 91%